White matter microstructure, white matter lesions, and hypertension: An examination of early surrogate markers of vascular-related brain change in midlife - Haight, Thaddeus; Nick Bryan, R.; Erus, Guray; Hsieh, Meng-Kang; Davatzikos, Christos; Nasrallah, Ilya; D'Esposito, Mark; Jacobs, David R.; Lewis, Cora; Schreiner, Pamela; Sidney, Stephen; Meirelles, Osorio; et al. (NeuroImage clinical, 2018)
We examined imaging surrogates of white matter microstructural abnormalities which may precede white matter lesions (WML) and represent a relevant marker of cerebrovascular injury in adults in midlife. In 698 community-dwelling adults (mean age 50 years ±3.5 SD) from the Coronary Artery Risk Development in Young Adults (CARDIA) Brain MRI sub-study, WML were identified on structural MR and fractional anisotropy (FA), representing WM microstructural integrity, was derived using Diffusion Tensor Imaging. FA and WML maps were overlaid on a parcellated T1-template, based on an expert-delineated brain atlas, which included 42 WM tract ROIs. Analyses occurred in stages: 1) WML were quantified for the different tracts (i.e., frequency, volume, volume relative to tract size); 2) the interdependence of FA in normal appearing WM (NAWM) and WML was examined across tracts; 3) associations of NAWM FA and hypertension status were assessed controlling for WML volume. In the latter analysis, both overall hypertension (i.e. hypertension vs. normotension and prehypertension vs. normotension) and hypertension categorized by antihypertensive treatment status (yes/no) and blood pressure control (e.g., diastolic <90 mmHg, systolic <140 mmHg), were assessed. WML were widely distributed across different WM tracts, however, WML volume was small. Mean NAWM FA was lower in participants with vs. participants without WML in given tracts. Hypertension was significantly associated with lower mean NAWM FA globally across tracts, both before and after adjustment for WML volume. Moreover, the magnitude of this association differed by treatment status and the level of control of the hypertension. In middle-aged adults, NAWM FA could represent a relevant marker of cerebrovascular injury when WML are minimally present. •Relations of white matter lesions (WML), fractional anisotropy in normal white matter tissue (NAWM FA), and hypertension status were examined for multiple WM tracts.•WML were widespread but overall WML burden was low.•Lower NAWM FA was associated with hypertension after accounting for WML.•NAWM FA could represent an early surrogate marker for vascular-related WM changes.